The Role of the Fashion Industry and Muslim Celebgrams in Constructing Contemporary Muslim Fashion Trends among Female Students - Zulfatun Ni'mah; Mahmud Arif; Chanif Ainun Naim; Rahmatullah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The widespread of the fashion industry, which heavily utilizes the Instagram platform for marketing, influences the trends of Muslim fashion. Additionally, the image presented by Muslimah influencers also contributes to shaping the standards of contemporary Muslim clothing. This study aims to explore the role of the fashion industry and the image of Muslimah influencers in constructing contemporary standards of Muslimah attire. The study focuses on observing this phenomenon among female students at Sunan Kalijaga State Islamic University Yogyakarta. By utilizing Giddens' theory of structuration with descriptive and interpretive analysis, the changes in contemporary Muslim fashion trends among female students are seen as outcomes of the process of structuration. The internal dynamics within Muslimah individuals who have a tendency to appear fashionable without compromising their religiosity serve as a form of self-identity representation. At the same time, there are external structures that also influence them in determining Muslimah clothing, namely the external factors of the fashion industry's role and influencer images. This article argues that fashion trends are created through the existence of agency factors, where the interests of the industry and influencers are involved.